CHILDREN AND THE DISEASE AND HOSPITALIZATION PROCESSES EFFECT (Fiep Bulletin - online, 2013)
A child hospitalization involves a moment that the child lives deeply: the disease process that results in corporal fragility; the outcrop of feelings, emotions and reactions after being removed from its social-cultural environment; changes in its rigid habits due to routines and rules; the carried through unfamiliarity before the used materials, techniques and procedures; that it sends it to a passive role and of discomfort, annulling its autonomy. There still are restrictions of the necessary stimuli to the continuity of the global development and excess of other stress factors. Therefore, it is important to point out consequences that can generate the delay in the child's neural-psycho-motor development, affect its psycho-affective maturation and lead to one intellectual deficit. Methodology: The present study aims to understand how diseases and hospitalization influence children by means of literature review and field research, carried through in two infantile hospitals, both in the city of Goiânia, between March and June of 2004. The data had been gotten by means of observation direct in - participant of the researcher and perception of the researcher during therapeutic attendance, of the diverse involved professionals in the hospital environment, as well as of the parents or companions during the different stages of the processes of disease and hospitalization, told verbally or in writing, more than entering 100 children taken care of and observed. The gotten data had been analyzed of descriptive and qualitative form. Conclusion: Observing the various effects originated from the processes of disease and hospitalization, the present study showed a need for acting in the hospital environment from the different health professionals, providing a better emotional state to the child; promoting global child development; humanizing procedures and environment; socializing children and their relatives, and also promoting experiences exchanges; hospital environment; strengthen the mother-child relationship, among other aspects aiming to promote life quality and health, promoting, as well, a pleasant memory from the hospitalization experience.
Keywords: disease; hospitalization; children.